β2-Adrenoceptors and GRK2 as Potential Biomarkers in Patients With Chronic Pulmonary Regurgitation - Rodriguez-Serrano, María; Rueda, Joaquín; Buendía, Francisco; Monto, Fermi; Aguero, Jaime; Osa, Ana; Cano, Oscar; Martínez-Dolz, Luis; D’Ocon, Pilar (Frontiers in Pharmacology, 2019)
Pulmonary regurgitation (PR) is a frequent complication after repair of congenital heart disease. Three different GRK isoforms (GRK2, GRK5 and GRK3) and two β-adrenoceptors (β1-AR and β2-AR) are present in peripheral blood mononuclear cells (PBMC) and their expression changes as a consequence of the hemodynamic and neurohumoral alterations that occur in some cardiovascular diseases. Therefore, they could be useful as biomarkers in PR. A prospective study was conducted to describe the expression (TaqMan Gene Expression Assays) of β-ARs and GRKs in PBMC isolated (Ficoll® gradient) from patients with severe PR before and after pulmonary valve replacement and establish if this expression correlates to clinical status. 23 patients with severe PR were included and compared with 22 healthy volunteers (controls). PR patients before the PVR had a significantly lower expression of β2-AR (478.0 ± 201.6 mRNA copies) vs. controls (812.6  497.23 mRNA copies), so as GRK2 expression (503.4  364.95 copies vs. 858.1  380.3 mRNA copies). The expression of β2-AR and GRK2 significantly decreases in symptomatic and asymptomatic patients, as well as in patients under treatment with beta-blockers and non-treated patients. The expression of β2-AR and GRK2 in PR patients recovers the normal values after pulmonary valve replacement (754,8  77,1 and 897,8 87,4 copies, respectively). Therefore, changes in the expression of β2-AR and GRK2 in PBMC of PR patients, could be considered as potential biomarkers to determine clinical decisions.